El croquis y el relevamiento de datos: elementos motivadores para la adquisición de competencias para los alumnos de Ingeniería - Herrera, Luis Alberto (2018)
This work will show a didactic experience carried out from the subject Systems of Representation of the Faculty of Exact Sciences and Technology of the National University of Tucumán with students of Engineering careers. The purpose of this experience was to encourage students to acquire professional skills (sketching and data gathering), through a practice that links graphic representation with reality close to students, and serves as a motivating element. The experience consisted in the survey of elements of reality of different complexity (three-dimensional elements chosen from the physical reality of the school's courtyard) with the dump on paper through quick drawings, the reproduction of the model on a larger scale (blackboard) and finally the representation of the same in paper in appropriate scale and properly delimited. In the experience, different instances of group and individual work were interspersed. Subjects belonging to the curriculum (projections and perspective) were addressed through practices that contribute to the acquisition of professional skills of engineers, through the development in the students of the observation capacity and synthesis capacity and the management of the proportions, as well as the internalization of the concept of scale and its application. It is considered that through these motivating activities, the idea of "learning by doing" is reinforced, and an added value is obtained linked to the competence of sketching and data gathering.